Improving Outcomes for English Learners Through Technology: A Randomized Controlled Trial. (June 2021) - Harper, David; Bowles, Anita R.; Amer, Lauren; Pandža, Nick B.; Linck, Jared A.
English learners (ELs) in K–12 schools must acquire English while simultaneously mastering content knowledge. Educational technology may support students' learning through the affordance of individualized language practice. The current randomized controlled trial intervention study examined the effects of Rosetta Stone Foundations software on English learning among middle school ELs. The study took place in Grades 6 to 8 of an urban U.S. school district ( N = 221). Predictors of interest included time of testing (pretest vs. posttest) and software usage, and covariates included grade level, sex, and attendance. Additionally, socioeconomic status and home language were accounted for due to sample homogeneity. Multilevel models indicated that treatment group students showed larger gains than control group students on oral/aural outcomes. These results indicate that the software intervention enables individualized practice that can produce proficiency-related gains over and above the typical classroom curriculum.